1982
DOI: 10.1021/bi00260a016
|View full text |Cite
|
Sign up to set email alerts
|

Role of poly(adenosine diphosphate ribose) in deoxyribonucleic acid repair in human fibroblasts

Abstract: We have investigated the role of poly(adenosine diphosphate ribose) in DNA repair in human fibroblasts by observing the effects of 3-aminobenzamide (3AB), a specific inhibitor of poly(ADP-ribose) synthesis, on various aspects of DNA repair. After treatment of human fibroblasts with dimethyl sulfate (DMS), 3AB retarded the joining of strand breaks; unscheduled DNA synthesis was unaffected after low doses of DMS but was stimulated after high doses. 3AB also enhanced the cytotoxicity of DMS. After gamma irradiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…Nate Acad ScL USA 81 (1984) 245 posed to radiation or chemicals at various doses were in the range of i0-4 to 10-2 foci per survivor and were higher in the hamster cells (Tables 1 and 2). BzA (1 mM) and 3ABzA (1 mM) had no influence alope but reduced transformation frequencies in both cell types for each damaging agent, with no significant effects on cell survival, unlike the increased toxicity seen in other cell types (18,19) (Tables 1 and 2). BzA and 3ABzA had essentially the same effect on transformation frequencies except for C3H lOT'/2 cells irradiated with x-rays (Table 1), in which BzA was more effective.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Nate Acad ScL USA 81 (1984) 245 posed to radiation or chemicals at various doses were in the range of i0-4 to 10-2 foci per survivor and were higher in the hamster cells (Tables 1 and 2). BzA (1 mM) and 3ABzA (1 mM) had no influence alope but reduced transformation frequencies in both cell types for each damaging agent, with no significant effects on cell survival, unlike the increased toxicity seen in other cell types (18,19) (Tables 1 and 2). BzA and 3ABzA had essentially the same effect on transformation frequencies except for C3H lOT'/2 cells irradiated with x-rays (Table 1), in which BzA was more effective.…”
Section: Resultsmentioning
confidence: 92%
“…When cells are exposed to DNA-damaging agents, single-strand breaks are produced in the DNA. The frequency of breaks represents a dynamic balance between rates of direct and enzymatic strand breakage and rates of ligation (16)(17)(18)(19)(20). A representative example of strand break measurements in C3H lOT'/2 cells is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A role for PARP-1 in the repair of DNA double-strand breaks (DSB) has also been suggested (14,15). However, PARP-1 À/À cells display normal DSB repair through nonhomologous end joining as well as homologous recombination (16), and it has been shown that PARP-1 is not involved in recovery from DSB induced by g-rays (17), etoposide (18), or neocarzinostatin (19); yet, post-transcriptional ADP-ribosylation of some repair proteins affects their DNA-binding ability and catalytic activity (6).…”
Section: Introductionmentioning
confidence: 99%
“…It inhibits the repair of DNA damage induced by various alkylating agents or by yirradiation. Previous reports suggest that it is the ligation of DNA during the repair process that is impaired (14)(15)(16)(17). In agreement with this suggestion, it has recently been shown that alteration of chromatin structure by poly(ADP-ribose) synthetase influences the activity of the DNA ligases (18).…”
mentioning
confidence: 99%